Dissecting the role of diabetes-associated PAX4 polymorphisms in modulating pancreatic beta cell development and function - Lau, Hwee Hui (Nanyang Technological University, 2023)
Diabetes is a major chronic disease with an excessive healthcare burden on society. A missense variant within the coding region of the PAX4 gene (rs2233580, R192H) is associated with T2D in East Asians. In mice, Pax4 is essential for beta cell formation but neither the role of diabetes associated variants in PAX4 nor PAX4 itself on human beta cell development and/or function are known. Our study demonstrates carriers of the PAX4 R192H or a novel Y186X allele(s) to have reduced beta cell function. Deletion of PAX4 in isogenic human induced pluripotent stem cell (hiPSC)-derived beta-like cells resulted in de-repression of alpha cell gene expression whilst in vitro differentiation of hiPSCs from carriers of R192H or Y186X allele(s) exhibited increased polyhormonal endocrine cell formation and reduced insulin content. Correction of the PAX4 variant allele(s) reversed these phenotypic changes. In the human beta cell model, EndoC-βH1, PAX4-knockdown led to impaired insulin secretion and reduced total insulin content. Together, we demonstrate the role of PAX4 in human endocrine cell development, beta cell function and its contribution to T2D risk.